The place of AI technologies in geological and information legal relations - Pashchenko, O. A.; Kirin, R. S.; Khomenko, V. L. (Аналітично-порівняльне правознавство, 2025)
The article analyzes the place and prospects of artificial intelligence (AI) in geological and information legal relations, which is a topical issue in the context of rapid development of digital technologies and their impact on geological science and legal practice. The article defines the role of AI technologies in processing geological data, forecasting geological processes and optimizing exploration and production of mineral resources, and also analyzes the legal, ethical and socio-economic aspects of their integration. The article discusses the theoretical foundations of geological and information legal relations, including their essence, subjects and objects, and analyzes the regulatory framework, in particular, international acts and national legislation of Ukraine. The author emphasizes their insufficiency for AI regulation. Particular attention is paid to the characteristics of geological information, such as large volume, complexity, and confidentiality, which create specific challenges for the use of AI. The article explores the role of AI in geological information processes, including automation of data collection and analysis, use of neural networks and deep learning for field modeling and seismic data analysis, and provides examples of practical applications of AI. At the same time, legal aspects such as AI regulation, allocation of responsibility for errors, protection of confidential geoinformation, and ethical issues related to algorithm transparency and data bias are highlighted. The challenges of AI integration are analyzed, including technical limitations, legal gaps, and socioeconomic consequences. Prospects for development are proposed, including the introduction of innovative AI technologies, the unification of international standards, and recommendations for improving legislation, including the certification of AI systems and data protection. The transformational role of AI in geological research and the need to harmonize legal regulation to ensure the ethical and efficient use of technologies are emphasized. Further areas of research include the assessment of data bias, the development of liability models, and international cooperation for AI standardization.